Status of literature in the age of global risks - Hajdu, Péter (Primerjalna književnost, 2009)
This paper scrutinises the possible connections of the diminished prestige of literature with globalisation, especially with the breakdown of nation building projects supported by elites, and with the demand of a spiritual-discursive self-understanding instead of a narrative one which characterises the reading strategies that made fiction popular.
Keywords: književnost; literature; nacionalna kultura; državotvornost; kozmopolitizem; globalizacija; globalization